Haemoglobin concentration and linear cardiac output, peripheral resistance, and oxygen transport. Issue 6525 (5th April 1986) - Daniel, M K; Bennett, B; Dawson, A A; Rawles, J M
Abstract : Increasing the haemoglobin concentration results in increased oxygen transport at the cost of increased blood viscosity. This suggested the concept of an optimum packed cell volume for maximising oxygen transport and a study was therefore conducted seeking supportive evidence. Linear cardiac output was measured as minute distance by Doppler ultrasound in 40 patients with haemopoietic disorders who had stable haemoglobin concentrations ranging from 30 to 200 g/l. The correlation between haemoglobin concentration and minute distance (r = -0.45; p less than 0.01) was negative, and correlations between haemoglobin concentration and mean blood pressure (r = 0.66; p less than 0.001) and haemoglobin concentration and peripheral resistance (r = 0.64; p less than 0.001) were positive. Calculated oxygen transport increased across the whole range of haemoglobin values. These results suggest that adjustment of peripheral resistance in response to oxygen availability overrides the influence of blood viscosity on cardiac output and that the optimum packed cell volume for oxygen transport is the highest that can be achieved.